The care needs of patients with idiopathic pulmonary fibrosis and their carers (CaNoPy): results of a qualitative study. Issue 1 (December 2015) - Sampson, Cathy; Gill, Ben; Harrison, Nicholas; Nelson, Annmarie; Byrne, Anthony
Abstract Background Idiopathic pulmonary fibrosis (IPF) is a chronic, fibrotic interstitial lung disease of unknown origin. It has a median survival of three years but a wide range in survival rate which is difficult to predict at the time of diagnosis. Specialist guidance promotes a patient centred approach emphasising regular assessment, information giving and supportive care coordinated by a multidisciplinary team (MDT). However understanding of patient and carer experience across the disease trajectory is limited and detailed guidance for MDTs on communication, assessment, and triggers for supportive and palliative interventions is lacking. This study addresses uncertainties relating to care needs of patients and carers at different stages of the IPF disease trajectory. Methods Following ethical approval a multi-centre mixed-methods study recruited participants with IPF at four stages of the disease trajectory. Qualitative analysis was used to analyse 48 semi-structured interviews with patients (27) and paired carers (21). Results Patients and carers outlined key elements of MDT activity capable of having significant impact on the care experience. These were structured around:Focus of clinical encounters Timely identification of changes in health status and functional activity Understanding of symptoms and medical interventions Coping strategies and carer roles. Conclusions Patients diagnosed with IPF have a clear understanding of their prognosis but little understanding of how their disease will progress and how it will be managed. In depth analysis of the experiences of patients and carers offers guidance for refining IPF clinical pathways. This will support patients and carers at key transition points in line with National Institute for Health and Care Excellence (NICE) guidance.